IMPROVING BREAST CANCER AWARENESS AMONG ADULT FEMALES IN MBINGO BAPTIST HOSPITAL COMMUNITY. - Bih , Remedy; Nalubega, Jane Frank; Kavuma, David; Okello, Elizabeth; Akankwasa, Edith (Student’s Journal of Health Research Africa, 2025)
Background Breast cancer awareness strategies have been proven to reduce breast cancer-related deaths in many countries worldwide. This project is ongoing, creating behavior change attitudes in most women in the community by empowering them to take responsibility for their breast health. Methodology This project used a logical framework with stakeholders and community involvement. Support groups and survivors to tell their stories, which acts as a boost to the project’s success. Choosing a change agent model with the help of Kotter’s change model facilitated in management of change in this process. The M & E structure has enabled the project sustainability with community training and retraining activities to “cause the change to stick”. Creating a conducive environment through good leadership, communication, and the motivation of team members further propelled the project from step to step. Results Learning lessons of tolerance, team building, resource management, and managing change cannot be overemphasized. This project opened avenues for further research. Granted more finances, many adult females accessing this community shall be reached, thereby promoting health through behavior change. Conclusion BC awareness continues to be the best strategy to fight and ensure early breast cancer diagnosis and treatment at MBH, Cameroon, Africa, and the world. This strategy has been proven to strengthen health systems and build communities through health promotion. Recommendation BCA campaigns should be implemented as part of a health promotion strategy aimed at enlightening communities about the dangers of late BC diagnosis